A familial study of twins with severe asthenozoospermia identified a homozygous SPAG17 mutation by whole‐exome sequencing. Issue 2 (4th September 2017) - Xu, X.; Sha, Y.‐W.; Mei, L.‐B.; Ji, Z.‐Y.; Qiu, P.‐p.; Ji, H.; Li, P.; Wang, T.; Li, L.
Abstract : Asthenozoospermia (AZS) is a common cause of male infertility, characterized by abnormal reduction in the motility of ejaculated spermatozoa. Here, in a patient from a consanguineous family, we identified a homozygous mutation (c.G4343A, p.R1448Q) in SPAG17 by whole‐exome sequencing. The encoded protein, SPAG17, localizes to the axonemal central apparatus and is considered essential for flagellar waveform. In silico analysis revealed that R1448Q is a potential pathogenic mutation. Immunostaining and western blot assays showed that the R1448Q mutation may exert a negative effect on the steady‐state of the SPAG17 protein. Therefore, SPAG17 may be a new pathogenic gene causing AZS. Abstract :